2011
DOI: 10.1124/dmd.111.040097
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Daikenchuto, a Traditional Japanese Medicine (Kampo) after Single Oral Administration to Healthy Japanese Volunteers

Abstract: ABSTRACT:The pharmacokinetics of daikenchuto (TJ-100), a pharmaceuticalgrade traditional Japanese medicine, were investigated in healthy Japanese volunteers after a single oral administration of 2.5-, 5-, and 10-g doses. Six ingredients [hydroxy-␣-sanshool (HAS), hydroxy-␤-sanshool (HBS), [6]-shogaol (6S), [10]-shogaol (10S), ginsenoside Rb 1 (GRB1), and ginsenoside Rg 1 (GRG1)] of TJ-100 were determined by using liquid chromatography-tandem mass spectrometry. The results indicated that HAS, an ingredient deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 17 publications
(15 reference statements)
3
46
0
Order By: Relevance
“…Similar to previous studies in humans (Munekage et al. 2011), in SPF mice Rb1 was slowly absorbed, peaked at 2 h, and decreased slowly. After 24 h, over 80% of the peak Rb1 amount was still present in the blood.…”
Section: Resultsmentioning
confidence: 93%
“…Similar to previous studies in humans (Munekage et al. 2011), in SPF mice Rb1 was slowly absorbed, peaked at 2 h, and decreased slowly. After 24 h, over 80% of the peak Rb1 amount was still present in the blood.…”
Section: Resultsmentioning
confidence: 93%
“…As reported previously in Japanese PK study (Munekage et al, 2011), nonlinearity was observed in AUC of GRB1, but dose-dependence in half-life was not; therefore, a nonlinear absorption model was assumed for the GRB1 analysis. As a result, nonlinear parameter (b) showed a significant value, and the AIC value indicated a better fit compared with the model not assuming the nonlinear parameter.…”
Section: Discussionmentioning
confidence: 91%
“…The concentrations of five DKT constituents-HAS, HBS, 6S, 10S, and GRB1-were determined by a validated liquid chromatography-tandem mass spectrometry method as reported by Munekage et al (2011). The limits of the quantification were 0.01 ng/ml for HAS, HBS, and GRB1 and 0.02 ng/ml for 6S and 10S.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, hydroxyl-α-and hydroxyl-β-sanshool were detected in human plasma and urine after oral administration of Daikenchuto. 5,6) Consequently, in terms of delineating the mechanism of action of Daikenchuto, hydroxyl-α-and hydroxyl-β-sanshool are considered key compounds. Total synthesis of hydroxyl-α-and hydroxyl-β-sanshool has not been reported.…”
mentioning
confidence: 99%